The Effect of Training and Leadership Development on Organisational Productivity - Zulaeha Rahmah Dewi; Ersa Hestiningrum; Aldilah Niken Riyani; Sabiani Nanda Ariyanti; Dinda Yulianti Rahayu; Ratih Ayu Sekarini (Indonesian Journal of Innovation Multidisipliner Research, 2025)
Human resources (HR) is a major factor in achieving organizational goals, and investment in training and leadership development is a crucial aspect in improving individual competence and organizational effectiveness. This study aims to deeply analyze the effect of training and leadership development on organizational productivity of the Student Executive Board of the Faculty of Economics, Islamic University of Jakarta (BEM FE UIJ). Using a quantitative approach, this study involved 32 respondents consisting of members of BEM FE UIJ. Data were collected through a survey using a questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression techniques using SPSS 25 software. The results showed that training has a positive and significant influence on organizational productivity (Sig. 0.008 <0.05), which indicates that a systematically structured training program can improve the skills and work effectiveness of organizational members. Meanwhile, leadership development also contributes positively to productivity, although it is not statistically significant (Sig. 0.078 > 0.05). Regression analysis shows that training and leadership development simultaneously have a significant influence on organizational productivity, with a coefficient of determination (R²) of 52.9%. This suggests that the two variables are able to explain most of the variability in productivity in organizations. Structured training effectively improves competencies, and leadership development adds value. This study underscores the importance of investing in training and leadership development to improve the performance of student organizations.